Mekanisme Kerja dan Target Molekuler Interleukin-1 receptor antagonist (Anakinra) pada Aterosklerosis - M. Yulis Hamidy (Jurnal Ilmu Kedokteran, 2017)
Inflammation plays an important role in the development and progression of a variety of cardiovascular conditions,most notably coronary atherosclerosis and congestive heart failure. A number of inflammatory molecules have beenimplicated in these processes, including interleukin-1 (IL-1). IL-1 receptor antagonist is an endogenous inhibitor of IL-1, which competitively binds to the IL-1 type I receptor without activating it. Anakinra is a nonglycosylated, recombinantform of human IL-1ra that, like endogenous IL-1ra, competitively inhibits IL-1 by binding the IL-1 type I receptor.